THE STRATEGIES AND CHALLENGES OF NON-GOVERNMENTAL ORGANIZATION ROLES IN FLOOD DISASTER MANAGEMENT IN JAKARTA - Hisyam Yusril Hidayat; Syarif Amr Hasyemi; Muhammad Galih Saputra (NATAPRAJA, 2020)
The paradigm shift in disaster management places non-governmental organizations (NGOs) as the actors who contribute to the process. However, NGOs still face many challenges both internally and externally. The author tries to find challenges from the role of NGOs and tries to formulate the right strategy. This research is categorized as a post-positivist paradigm and uses a mixed active method. The NGOs analyzed were Yayasan Peta Bencana and MPBI. The results show that there are internal and external challenges. The challenges are the number of volunteers are limited, lack of volunteer knowledge, there is no program evaluation, and financial accountability from NGOs. Meanwhile, external environmental barriers are still low in understanding and role of society and the contribution of the private sector is still low. The authors formulate nine strategies to overcome these problems. A limitation in this study is that researchers only use secondary data to explain the role of either the government or other actors.